Cambridge primary Mathematics learner$1 (Bs book stage 1/s - Moseley, Cherri; Rees, Janet (New York : Cambridge, 2014)
Cambridge Primary Mathematics Learner$1 (Bs Book Stage 1 introduces young learners to basic mathematical concepts through hands-on activities, visual learning, and problem-solving exercises. It follows the Cambridge Primary Mathematics curriculum and encourages critical thinking and confidence in using numbers.s
Keywords: Mathematics -- Study and teaching -- Problem solving -- Numeracy skills